Analysis of Portfolio Expected Returns as a Material Consideration for Investors in Choosing Investments in the Pandemic Period (Formation of Optimal Portfolios Using the Black Litterman Model on Hang Seng Stocks for the 2017-2019 Period): Analisis Penilaian Expected Return Portofolio Sebagai Bahan Pertimbangan Investor dalam Memilih Investasi di Masa Pandemi (Pembentukan Portofolio Optimal Dengan Model Black Litterman pada Saham Hang Seng Periode 2017-2019) - Wiji Rahayu; Wiwit Hariyanto (Academia Open, 2021)
. This study attempts to find out how a method of Black Litterman in the formation of stock portfolios. This research was conducted on the basis of increasing the number of investors' funds in the capital market for certain stocks, showing that it increases positive sentiment on stock investments compared to other investments. The Black Litterman Model method is one of the options that can be used in the formation of portfolio. The Black Litterman model method is a method that formulates the existence of an element of return equilibrium and investor views in an investment. By using the Black Litterman Model, investors can take advantage of all available information as the basis for forming a maximum portfolio. The object of this research is Hang Seng (HSI) stock price data for the period 2017 – 2019. The research sample is 35 companies. The results of this study resulted in 10 stocks included in the Black Litterman model portfolio with the expected return on the portfolio (which consisted of 10 stocks with the Black Litterman model) of 0.062387. Where the highest proportion of returns given by Shenzhou International Group Holdings Limited (SEHK: 2313) is 23% and the expected return is 0.017933. While the lowest level is occupied by New World Development Company Limited (SEHK: 17) with a proportion of 1% and an expected return of 0.000687.